Efficacy of Integrated Traditional Chinese and Western Medicine for Treating COVID-19: A Systematic Review and Meta-Analysis of RCTs - Yin, Bei; Bi, Yi-Ming; Sun, Lu; Huang, Jin-Zhu; Zhao, Jia; Yao, Jia; Li, An-Xiang; Wang, Xian-Zhe; Fan, Guan-Jie (Frontiers in Public Health, 2021)
Methods: In this meta-analysis, we searched PubMed, Embase, Web of Science, SinoMed, CNKI, CQVIP, and Wanfang Databases from inception until April 12 2021 to identify randomized controlled trials (RCTs) of Integrated Medicine in the treatment of COVID-19. RevMan v5.3 and Stata software were used for statistical analysis. Results: A total of 1853 patients with COVID-19 were enrolled in 19 RCTs. Meta-analysis results showed that Integrated Medicine therapy was statistically significant and was associated with improvements in clinical symptoms, including fever disappearance rate [RR = 1.25, 95% CI: (1.04, 1.50), P = 0.02], fatigue disappearance rate [RR = 1.28, 95% CI: (1.00, 1.63), P = 0.05], overall effective rate [RR = 1.17, 95% CI: (1.10, 1.26), P < 0.00001], and chest CT improvement rate [RR = 1.24, 95% CI: (1.14, 1.34), P < 00001], as well as laboratory indicators; for example, CRP [WMD = −4.14, 95% CI: (−6.38, −1.91), P = 0.0003], WBC [WMD = 0.35, 95% CI: (0.11, 0.58), P = 0.004], and LY count [WMD= 0.32, 95% CI: (0.12, 0.52), P = 0.001]. In addition, our imprecise results also showed that Integrated Medicine did not improve the cough disappearance rate [RR = 1.28, 95% CI: (1.00, 1.63), P = 0.05], ESR [WMD = −14.97, 95% CI: (−33.67, 3.72), P = 0.12] and PCT [WMD = −0.01, 95% CI: (−0.03, 0.01), P = 0.16] compared with conventional Western medicine (CWM). Subgroup Analysis showed that the effect of Integrated Medicine is more obvious in improving symptoms when the treatment time is less than 2 weeks. For patients with severe and non-severe COVID-19, Integrated Medicine is more effective in improving fever and cough symptoms than using CWM. Conclusion: The results of the current meta-analysis suggested that the Integrated Medicine can improve the clinical symptoms, chest CT and infection indicators of COVID-19 patients. Even if the treatment time is less than 2 weeks, compared with CWM treatment, the effect of Integrated Medicine in improving symptoms is more obvious. However, the results should be interpreted cautiously due to the heterogeneity among the studies.